Administrative and Compliance Costs of Value Added Tax (VAT): A Review. Issue 2 (December 2021) - Vishnuhadevi, S.
This article surveys the existing literature on the compliance and administrative costs of VAT incurred by the businesses and the governments respectively. The review focuses on the concepts and components of VAT operating costs, the link between the tax compliance costs and the tax compliance decision, factors associated with compliance costs and the steps taken by various countries to mitigate these costs. The major studies of VAT compliance cost since 1980 and the methodologies adopted are summarised. The review of the studies shows that the VAT compliance costs are higher and significant in both absolute money terms and relative to tax revenue in developed as well as developing countries than the administrative costs and the compliance costs are highly regressive in nature which disproportionately affects the small businesses. Further, the psychological costs are underexplored in the VAT compliance cost literature due to the difficulty in measuring them. This article also highlights the understudied area of VAT compliance costs in India and the importance of exploring the compliance burden in India.